2018
DOI: 10.1074/jbc.ra118.004788
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial inner membrane protein MPV17 prevents uracil accumulation in mitochondrial DNA

Abstract: Mitochondrial inner membrane protein MPV17 is a protein of unknown function that is associated with mitochondrial DNA (mtDNA)-depletion syndrome (MDS). MPV17 loss-of-function has been reported to result in tissue-specific nucleotide pool imbalances, which can occur in states of perturbed folate-mediated one-carbon metabolism (FOCM), but MPV17 has not been directly linked to FOCM. FOCM is a metabolic network that provides one-carbon units for the de novo synthesis of purine and thymidylate nucleotides (e.g. dTM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 39 publications
3
32
0
Order By: Relevance
“…This result is in agreement with the work of Dalla Rosa and collaborators who showed that proliferating fibroblasts from MPV17-deficient patients do not display any reduced mtDNA content [9]. It is also in accordance with the recent work of Alonzo and collaborators who did not find any reduction of mtDNA content in MPV17-silenced HeLa cells [12].…”
Section: Mpv17 Silencing Is Not Associated With Mtdna Copy Number Depsupporting
confidence: 93%
See 3 more Smart Citations
“…This result is in agreement with the work of Dalla Rosa and collaborators who showed that proliferating fibroblasts from MPV17-deficient patients do not display any reduced mtDNA content [9]. It is also in accordance with the recent work of Alonzo and collaborators who did not find any reduction of mtDNA content in MPV17-silenced HeLa cells [12].…”
Section: Mpv17 Silencing Is Not Associated With Mtdna Copy Number Depsupporting
confidence: 93%
“…In this work we studied the putative role of MPV17 in cancer cell proliferation. While MPV17 silencing did not lead to depletion of mtDNA content in the tested cancer cell lines, in accordance with literature [9] [12], the resulting proliferation phenotypes associated with MPV17 shRNA-mediated knockdown were unsettling and inconclusive, leading us to perform a rescue experiment that eventually excluded a role of MPV17 in cancer cell proliferation. The intriguing and somewhat misleading results we obtained during this investigation clearly demonstrate the need to systematically perform a rescue experiment in order to ascertain the specific nature of the experimental results.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Accordingly, high levels of rGTP were detected in mtDNA from Mpv17 -/livers (Moss et al, 2017). Other data showed that reduced MPV17 expression was associated with impaired dTMP synthesis without affecting de novo or salvage synthesis of dTMP, suggesting that MPV17 may be involved in maintaining dTMP levels in mitochondria through a still uncharacterized pathway, which may be involved in transporting dTMP or one of its precursors from the cytosol to mitochondria (Alonzo et al, 2018). In zebrafish, Mpv17 has been related to pyrimidine nucleotide metabolism via impairment of dihydroorotate dehydrogenase (Martorano et al, 2019).…”
Section: Introductionmentioning
confidence: 95%